Atrial cardiomyopathy — a new concept with a long history - T. G. Vaikhanskaya; T. V. Kurushko; Yu. A. Persianskikh; L. N. Sivitskaya (Российский кардиологический журнал)
Atrial cardiomyopathy (ACM) is a relatively common but clinically underestimated disorder, which is characterized by an increased atrial size and dysfunction. Previously, ACM was considered a primary disorder, but in 2016 this concept was revised by European Heart Rhythm Association (EHRA) working group with inclusion of secondary atrial remodeling. The EHRA document details aspects of atrial anatomy and pathophysiology, proposes definitions of ACM, histological classification, outlines the molecular mechanisms of atrial arrhythmia and the problems of personalized treatment and optimization of indications for catheter ablation.Practical application of the proposed ACM classification system, the clinical significance of novel ACM concept and the potential role of this information for a practitioner are presented in this article. Two clinical cases of ACM with “primary” (familial form of ACM due to NPPA gene mutation with primary defect in atrial structure and function) and “secondary” atrial remodeling (ACM caused by a longterm supraventricular tachyarrhythmias due to SCN1B gene mutation).